MODEL PERAN : SOLUSI INOVATIF DALAM MENINGKATKAN AKTIVITAS DAN KETERAMPILAN BERFIKIR KRITIS SISWA SD PADA PEMBELAJARAN MATEMATIKA - Rosha Amelya; Celia Cinantya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low level of activity and critical thinking skills of students in the learning process. The main focus of this research is the application of the ROLE combination model in learning in grade V of elementary school. This research involved 18 grade V students as research subjects. The type of research used is Classroom Action Research (CAR) by adopting the Kurt Lewin model and implemented for four meetings. Efforts made to overcome these problems are by implementing the ROLE combination model. The purpose of this study is to describe the activities and critical thinking skills of students during mathematics learning using the ROLE model, which is a combination of the PBL, AIR, and TGT models, in grade V of SDN Berangas 1 consisting of 18 students. This study uses the Classroom Action Research (CAR) method. The results of the CAR that have been implemented for four meetings show a significant increase in each meeting, both in terms of activity and students' critical thinking skills. Student activity has achieved success indicators, where most students are included in the active and very active categories with a percentage of 88%. Likewise, students' critical thinking skills have met the success indicators, with most students in the critical and very critical categories, also with a percentage of 88%. Thus, this ROLE model can be used as a reference and innovation in learning to improve students' critical thinking activities and skills.